Biobank Digitalization: From Data Acquisition to Efficient Use - Anastasiia S. Bukreeva; Kristina A. Malsagova; Denis V. Petrovskiy; Tatiana V. Butkova; Valeriya I. Nakhod; Vladimir R. Rudnev; Alexander A. Izotov; Anna L. Kaysheva (Biology)
Biobanks are involved in a broad range of studies, including both basic and clinical research, so their functions and roles are evolving. Digital biobanks have emerged due to digitalization in this field; however, it also entails an increasing number of ethical and legal issues, in particular those related to the protection of donor data and potential commercial applications. The development of biobanks and the size of stored datasets lay the groundwork for proceeding to digital biobanks that intensely employ artificial intelligence tools. Digital biobanks can simplify the search for and access to biological specimens, thus contributing to the conduction of research and creating new collaborations. They are becoming an increasingly important tool for personalized medicine and an individualized approach to disease treatment, contributing to the elaboration of more accurate diagnostic methods and the development of innovative therapeutic strategies.